Interprofessional Collaborative Education for Substance Use Screening: Rural Areas and Challenges - Kathryn R Puskar; Heeyoung Lee; Ann M Mitchell; Irene Kane; Susan A Albracht; Linda Rose Frank; Holly Hagle; Dawn Lindsay; Martin P Houze (Rural Nurse Organization; Binghamton University, 2016)
Purpose. Interprofessional collaborative practice (IPCP) has been advocated to overcome challenges related to rural healthcare and substance abuse. The investigators evaluated the effectiveness of an online interprofessional education (IPE) program to improve health care professionals' perceptions in treating people with substance use and identified the challenges of conducting IPE.   Sample. Sample included 106 healthcare professionals (nurses, behavioral health counselors, and public health workers) from rural areas in Pennsylvania, Ohio, and West Virginia. Method. This prospective study utilized a quasi-experimental design with healthcare professionals who received a 6-hour online IPE regarding substance abuse. Measures were the Alcohol & Alcohol Problems Perception Questionnaire (AAPPQ) and the Drug & Drug Problems Perception Questionnaire (DDPPQ). Findings. Perceptions of alcohol (i.e., role adequacy and role support) and drug (i.e., role adequacy, role legitimacy, sole support, and work satisfaction) problems were improved after training (Ps < .05). Competing priorities, leadership support, technology, rural culture, and fiscal consequences were addressed as challenges during project implementation. Conclusion. The IPE program improved the participants' attitudes and perceptions toward working with patients who struggle with substance abuse. Rural nurse managers can influence professionals in a range of clinical team settings to improve safety and quality of health care through IPCP. Challenges experienced by rural healthcare professionals can be resolved by the leadership support. Consequently, the leadership of nurse management can favorably impact patient healthcare outcomes by reinforcing IPE.  DOI:  http://dx.doi.org/10.14574/ojrnhc.v16i1.385